IMPROVEMENT OF PHYSICS CONCEPT MASTERY AND PEDAGOGY SKILLS THROUGH ANDROID-BASED ASSESSMENT LINK PRACTICES - Prastowo, Tjipto; Habibulloh, Muhammad; Fahmi, Muhammad Nurul; Realita, Arie; Anggaryani, Mita (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2025)
In the digital era of education, technology-enhanced learning has been increasingly important. As part of a teaching-learning process in schools and universities, the use of Android-based smartphones to strengthen concept mastery and pedagogy skills is challenging. In this context, this study explores Assessment Link in Physics, an Android-supported running application. This application was used to analyse high-school physics problems in two sets of exercises and a Quiz using the revised Bloom’s Taxonomy. Participants involved were 15 physics teachers from various senior high-schools in Tuban, East Java. Regarding the mobile apps, this study aims to examine the respondents’ perceptions on benefit, ease of use, and content of the apps. From a completed series of tests, where a positive trend was obtained (increasing mean scores of 71 and 80 in Problem Sets 1 and 2 to be 88 in Quiz) with the scores of the Quiz ranged between 79-96, much better than those of the preliminary tests, we conclude that the apps is successful to improve physics concept mastery and pedagogy skills, consistent with information from a filled three-in-one questionnaire, where all the respondents agree well with the benefit, ease of use, and content of the application. The results provide insight into the development of the existing mobile apps-supported learning for further work on STEM and TPACK projects introduced to students at all levels of education. ABSTRAK Dalam era pendidikan digital dan modern, pembelajaran berbasis teknologi semakin penting. Sebagai bagian dari proses belajar mengajar di sekolah dan universitas, penggunaan gawai berbasis Android untuk penguatan konsep dan keterampilan pedagogi adalah menantang. Dalam hal ini, studi ini mengeksplorasi Assessment Link in Physics, aplikasi berbasis Android yang dirancang untuk meningkatkan penguasaan konsep fisika dan keterampilan pedagogi melalui analisis soal fisika SMA dalam bentuk dua kali latihan dan satu kali tes berdasarkan Taksonomi Bloom revisi. Responden yang terlibat adalah 15 orang guru fisika SMA dari berbagai sekolah menengah atas di Tuban, Jawa Timur. Penelitian ini bertujuan untuk menguji persepsi responden terhadap keunggulan, kemudahan, dan konten aplikasi saat digunakan untuk meningkatkan keterampilan kognitif dan pedagogi. Dari serangkaian tes, dimana tren positif hasil tes diperoleh (ada peningkatan skor rerata dari 71 dan 80 pada Problem Set 1 dan 2 menjadi 88 pada Quiz merupakan respons sangat baik terhadap pembelajaran berbantuan gawai) dengan skor Quiz bervariasi antara 79-96, jauh lebih baik dibandingkan dengan skor tes pendahuluan, kami menyimpulkan bahwa Assessment Link in Physics berhasil meningkatkan penguasaan konsep fisika dan keterampilan pedagogi. Hal ini sesuai dengan informasi yang dikumpulkan dari kuesioner, dimana semua responden setuju dengan manfaat, kemudahan penggunaan, dan konten aplikasi. Hasil-hasil penelitian memberikan wawasan pengembangan lebih lanjut pembelajaran berbantuan gawai untuk implementasi proyek STEM dengan pendekatan TPACK yang diperkenalkan kepada seluruh siswa pada semua jenjang pendidikan.